PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR SCIENCE SISWA KELAS IVA SD NEGERI 005 KOTA MEDAN KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Junaiti Junaiti; Jesi Alexander Alim; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: the goal of this reearch is to increasing the result of student’s ability of IPA subject on SDN 005 Kotamedan 2014/2015. The subject of this research are all of students in class IV A on SDN 005 Kotamedan that consist of 17 students. This research is collaborative action class reseach with twos cycles. The result of this research had been upgrading which the average point of teacher activity on first cycle is 62,49%. The average point on second cycle is 79,16%. The average point of student,s activity on first cycle is 56,24%. The average point of student,s activity on second cycle is 81,24%. The data had been upgrading which before use cooperative model type numbered heads together 5 only students that completed (29,41%) that average 62,94. On first cycle had been upgrading until 11 students (64,70%) with average (70,88). On second cycle had been upgrading until 17 students (100%) with average 84,41. So all of upgrading is 34,11%. So that, it can concluded that the hypothesis of this research is” if applied cooperative model type numbered heads together, it can increase the result of IPA subject on class IV A SDN 005 Kotamedan” can accepeted.Keyword : cooperative model type numbered heads together, the result of IPA subject